Evaluación de las propiedades físico-mecánicas de hilos obtenidos a partir de la lana de oveja (Ovis orientalis aries) posterior a la aplicación de un agente blanqueador obtenido a base de diferentes concentraciones de peróxido de hidrógeno y ortiga blanca (Lamium álbum L.) - Janeta Ordoñez, Anthony Jhosue (2024)
Sheep wool is a natural fiber obtained from sheep fleece. It is one of the fibers most used by humans since ancient times, due to its physical-mechanical properties. Its chemical composition is characterized by keratin protein, which is covered by scales called cuticle, which gives it greater resistance, making it a unique fiber for the textile industry. The objective of this study was to evaluate the physical-mechanical properties of yarns obtained from sheep wool (Ovis orientalis aries) after the application of a bleaching agent, elaborated with different concentrations of hydrogen peroxide and white nettle (Lamium album). Two methods were used to obtain the extracts: infusion and decoction, which are commonly used in the Andean zones of Ecuador. To formulate the bleaching agent, different concentrations of extract and hydrogen peroxide were used, in addition to applying these two individually. The fiber was bleached at a temperature of 60°C for 30 minutes, which proved to be the appropriate conditions for the fiber not to be affected by temperature. Consequently, the whiteness index and yellowness index were evaluated to determine the efficiency of the different treatments. The resulting fibers were spun on a spinning wheel, where the treated filaments were twisted by the rotation and wound on a bobbin, which allowed the formation of yarns. Subsequently, their physico-mechanical properties were analyzed on the EZ-S SHIMADZU Universal Machine. Repeated measures ANOVA analysis of variance and Tukey's test (p < 0,05) were applied to evaluate if there were significant differences between the different treatments. The combination of white nettle extracts with hydrogen peroxide, compared to the control treatment, indicated that the lower the concentration of hydrogen peroxide and the higher the concentration of white nettle extracts, the higher the whiteness index and the lower the yellowness index. Despite this, the physico-mechanical properties were affected by the presence of hydrogen peroxide in the bleaching agent, since it alters the fiber structure, weakening it. In contrast, the exclusive use of white nettle extracts contributed to higher whiteness indexes with respect to crude fiber, but lower compared to the control treatment and the other treatments in which it was combined with hydrogen peroxide. However, its physico-mechanical properties, such as diameter, breaking strength, maximum displacement, maximum deformation, and alkali resistance, were superior due to the absence of hydrogen peroxide, which is responsible for weakening the fiber. Thus, this process is emerging as a viable alternative, in line with new trends in the textile industry.